Community ButterflyScaping: How to Move Beyond Butterfly Gardening to Create a Large-Scale Butterfly Habitat - Kathy C. Malone; Wendy Wilber; Gail Hansen; Jaret C. Daniels; Claudia Larsen; Esen Momol (EDIS)
ENH1160, a 20-page illustrated fact sheet by Kathy C. Malone, Wendy Wilber, Gail Hansen, Jaret C. Daniels, Claudia Larsen, and Esen Momol, provides developers, community associations, and homeowners with guidance in planning the vegetation in common areas, stormwater management systems, undeveloped areas, and yards to form large-scale habitats attractive to butterflies, pollinators, birds, and other local wildlife. Includes references. Published by the UF Department of Environmental Horticulture, September 2010.